(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
A heterotopic pregnancy is a rare complication of pregnancy in which both extra-uterine (ectopic pregnancy) and intrauterine pregnancy occur simultaneously. The prevalence of heterotopic pregnancy is estimated at 0.6- 2.5: 10,000 pregnancy. It is a challenge for obstetrician to manage the tubal pregnancy without interruption of intrauterine pregnancy. Here we describe a case who had left tubal alive ectopic pregnancy & also intrauterine alive pregnancy simultaneously after a natural conception. This patient was managed successfully with laparoscopic left salpingectomy, and intrauterine pregnancy has been continuing. There are some precautions during laparoscopic procedure & post operative period which can help for continuation of intrauterine pregnancy. In our clinical experience, this is an extreme rare disorder and we feel interest to report this case. A heterotopic pregnancy can result from a natural conception; it requires a high index of suspicious for early and timely diagnosis; a timely intervention can result in a successful outcome of the intrauterine fetus. J Bangladesh Coll Phys Surg 2016; 34(4): 218-221